A Barometer Of Entrepreneurial Dynamics Above The Crisis - Irina M. Drăgan; Alexandru Isaic-Maniu (Revista Română de Statistică, 2013)
In this paper, the analysis is performed for Romania where, after 50 years of communism, the free market economy, based on the free initiative of entrepreneurship, has been returned. The implementation of a scientific management generating performances that can lead the sector of SMEs to the requests of the Lisbon Strategy, cannot be completed without the existence of well-trained entrepreneurs, capable to improve their skills in modern management, thus leading to competitive results in a highly competitive market. Therefore, we consider in our paper some relevant indicators such: the evolution of new founded enterprises, the entrepreneur’s socio-professional profile, the entrepreneur’s level of education and new enterprise foundation rate. The analysis performed by this research allows us to formulate, synthetically, strengths and weaknesses in the entrepreneurial evolution for the period 1995-2011. Also, this study reveals the dependency between the economic growth, measured by GDP, and the rate of newly founded enterprises. The dynamic of new companies provides information both on the crisis ending and the resumption of economic growth.